PELAYANAN TERPADU KORBAN KEKERASAN TERHADAP PEREMPUAN DI KOTA SEMARANG - Marsha Ayunita Irawati (NATAPRAJA, 2015)
This study aims to analyze the effort that has been done by Women Empowerment,Child Protection and Family Planning Bureau (BP3AKB) of Semarang city. This is aqualitative research. The technique of collecting data employed interviews, documentation,book references, and related agencies official documents. The results showed that: a)SERUNI service center is not optimal, can be seen from number of violence against womenstill remains high from year to year. b) Limited mentor in SERUNI service center that werelacking, budget to handling are less dan facilities and infrastructure to reporting andassistance is good enough. c) Factors that affect the handling of violence against women inSemarang City is the quantity of human resources are inadequate, the commitmentIntegrated SERUNI service centers to provide maximum services to victims of violence,lack of budget assistance, facilities and infrastructure SERUNI service centers inadequate,lack of awareness and community participation in the elimination of violence againstwomen, characteristics abusers are difficult to handle, and Semarang as destination forjob seekers.Keywords: Public Service, Violence Against Women, Affecting Factors